My American journey - Powell, Colin L. (New York : Ballantine Books, 1996)
The former chairman of the Joint Chiefs of Staff recalls his youth, his military service, and his rise to the heights of America's political and military elite.
Luther and Arie's son - A soldier's life for me - Courting Alma - "It'll take half a million men to succeed" - Coming home - Back to Vietnam - White House fellow - "Go, gunfighter, go!" - The graduate school of war - In the Carter Defense Department - The Reaganites - and a close call - The phone never stops ringing - "Frank, you're gonna ruin my career" - National security advisor to the President - One last command - "Mr. Chairman, we've got a problem" - When you've lost your best enemy - A line in the sand - Every war must end - Change of command - Mustering out - A farewell to arms - Afterword - Colin Powell's rules.
Includes index.
Keywords: Generals -- United States -- Biography